2017
DOI: 10.1136/ejhpharm-2016-001134
|View full text |Cite
|
Sign up to set email alerts
|

UK hospital patient discharge: the patient perspective

Abstract: ObjectivesHospital discharge is a complex process that can result in errors and delays for patients, particularly around the supply of medicines and communication of information. To improve patient discharge, patient perspectives of the discharge service must be explored to determine where patients feel problems arise. This study aimed to explore inpatient perceptions and experiences of the current discharge process. MethodsThis study involved questionnaires with patients at a large city centre teaching hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…The current study sheds light on several issues related to patients’ perceptions regarding counselling about medications and SDM and their awareness of community pharmacy services that could enhance understanding of their medications and conditions. The generated results clearly identified that there is a lack of detailed medication counselling and patients’ involvement in SDM, which echo previous findings in the literature [ 5 , 25 ]. Underutilisation of community pharmacy services was also highlighted in this study by the lack of awareness among target patients about services related to medication optimisation and counselling which can be promptly and easily accessible at primary care level.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The current study sheds light on several issues related to patients’ perceptions regarding counselling about medications and SDM and their awareness of community pharmacy services that could enhance understanding of their medications and conditions. The generated results clearly identified that there is a lack of detailed medication counselling and patients’ involvement in SDM, which echo previous findings in the literature [ 5 , 25 ]. Underutilisation of community pharmacy services was also highlighted in this study by the lack of awareness among target patients about services related to medication optimisation and counselling which can be promptly and easily accessible at primary care level.…”
Section: Discussionsupporting
confidence: 86%
“…A new finding revealed in this study was patients’ preference for receiving their discharge medications from community pharmacies. This could provide a solution for the delay in discharge related to the long wait for discharge medications highlighted in the literature [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the study of 104 medical and surgical inpatients, which highlight the lack of patients’ involvement with their healthcare decision. Only 22% of the participants reported participation with the decision making about their discharge and commented that they were sent home too early (Wright, Morecroft, Mullen, & Ewing, ). To increase their health knowledge, our study participants accessed informal information source like the internet to self‐manage their recovery and to influence their decision for seeking help after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the study of 104 medical and surgical inpatients, which highlight the lack of patients' involvement with their healthcare decision. Only 22% of the participants reported participation with the decision making about their discharge and commented that they were sent home too early (Wright, Morecroft, Mullen, & Ewing, 2017 2014), and provided online tools and resources to support consumers to be active participant in their healthcare decisions. Though we did not specifically explore patients' health literacy and their role in the decision making of their care in this study, it has been suggested that increasing patients' level of health literacy enables them to play a more active role in the decision making of their health process (Brabers, Rademakers, Groenewegen, van Dijk, & de Jong, 2017).…”
Section: Patients' Participation and Health Literacymentioning
confidence: 99%
“…Wright and colleagues1 report on a single-centre survey of inpatient perceptions and experiences of the current discharge process, and identify improvement opportunities in relation to waiting for medicines and lack of counselling by pharmacists. Problems such as low awareness among inpatients of pharmacy services or pharmacists citing challenges to achieving patient medication counselling have been reported internationally 2 3…”
mentioning
confidence: 99%